2012
DOI: 10.1016/j.expneurol.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of neuroplasticity

Abstract: Whether dramatic or modest, recovery of neurological function after spinal cord injury (SCI) is greatly due to neuroplasticity -the process by which the nervous system responds to injury by establishing new synaptic connections or by altering the strength of existing synapses. However, the same neuroplasticity that allows locomotor function to recover also produces negative consequences such as pain and dysfunction of organs controlled by the autonomic nervous system. In this review we focus specifically on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 85 publications
(103 reference statements)
0
50
0
Order By: Relevance
“…Furthermore, while we have applied this protocol to visualize engulfment of synapses during developmental synaptic remodeling in the healthy CNS, this protocol can also be applied in disease models. In particular, this protocol can be used to study diseases in which synapses undergo substantial remodeling, such as in the case of synapse loss and regeneration following spinal cord injury, early synapse loss associated with Alzheimer's disease, etc 12,[14][15][16][17][18][19][23][24][25][26] . In addition, one may also adapt this technique to study diseases in which phagocytosis of material other than synapses has been described, such as microglia/macrophage-mediated engulfment of myelin in demyelinating disease (e.g., multiple sclerosis) and engulfment of beta-amyloid in Alzheimer's disease 5,6,[27][28][29] .…”
Section: Broader Applications: Live Imaging and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while we have applied this protocol to visualize engulfment of synapses during developmental synaptic remodeling in the healthy CNS, this protocol can also be applied in disease models. In particular, this protocol can be used to study diseases in which synapses undergo substantial remodeling, such as in the case of synapse loss and regeneration following spinal cord injury, early synapse loss associated with Alzheimer's disease, etc 12,[14][15][16][17][18][19][23][24][25][26] . In addition, one may also adapt this technique to study diseases in which phagocytosis of material other than synapses has been described, such as microglia/macrophage-mediated engulfment of myelin in demyelinating disease (e.g., multiple sclerosis) and engulfment of beta-amyloid in Alzheimer's disease 5,6,[27][28][29] .…”
Section: Broader Applications: Live Imaging and Diseasementioning
confidence: 99%
“…In addition to these roles in the healthy nervous system, synaptic remodeling is also involved in nervous system disease/injury 12,14,15 . For example, following spinal cord injury, severed axons must subsequently remodel and form new synapses to achieve functional recovery [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinnervation of these axons onto neurons within the deeper dorsal horn was thought to be one of the primary mechanisms by which NGF leads to the establishment of chronic pain (Christensen and Hulsebosch 1997b; Romero et al, 2001; Brown and Weaver, 2012). Indeed, we previously observed that co-application of Semaphorin 3A with NGF in uninjured rats was capable of reducing sprouting and mechanical hyperalgesia (Tang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Plasticity may be a response to rewarded behavior, a change in maintenance of previously acquired behaviors, or just a by-product of activity (Wolpaw, 1997). Plenty of examples illustrate the dark side of this potentially beneficial phenomenon: focal dystonia in musicians (Classen, 2003); tinnitus (Pantev et al, 2012), poor recovery from spinal cord injury (Brown and Weaver, 2012) are all laid at the feet of plasticity, and judging by the distribution of agerelated differences in the brain, regions that retain greater plasticity may also be especially prone to age-related vulnerability (Raz et al, 1997;2001). Thus, while the research efforts concentrate on finding ways to maintain and promote plasticity throughout the adult life span, more attention should be paid to unintended consequences of manipulation of plasticity in adulthood.…”
mentioning
confidence: 99%